Assessing the mechanisms behind sound-taste correspondences and their impact on multisensory flavour perception and evaluation - Wang, Q (2017)
Recent research has shown that food and beverage perception can be influenced by means of aromas, shapes, colours, and even sounds (e.g. Auvray & Spence, 2008; Spence & Piqueras-Fiszman, 2014). Over-and-above any sounds involved in the eating process, various studies have begun to demonstrate the relationship between auditory attributes and taste/flavour perception. This thesis examines crossmodal correspondences – defined as the often-surprising associations between basic attributes of different sensory modalities – between sounds and tastes/flavours. The results reported here demonstrate that participants can make non-random matches between sound and a range of taste/flavour attributes including basic tastes, creaminess, spiciness, and even temperature. Moreover, soundtracks that are congruent with specific taste/flavours are demonstrated to influence food/drink evaluation (the "sonic seasoning" phenomenon). Most importantly, this thesis highlights the multiple pathways by which sonic seasoning might occur. Mirroring the role of food-related auditory cues (such as the sizzle of the steak), soundtracks that can shape our sensory expectations before tasting as well as focus our attention on specific tastes/flavours during tasting. In addition, the emotions evoked by the soundtracks can also be transferred to the food that one happens to be eating. The results are discussed in terms of theoretical implications, practical applications, and directions for future research.